Unveiling the dark side of Prevotella: a case of fatal pneumonia from a common probiotic - Li, Meng-Jie; Zhou, Shou-Feng; Zhang, Yu; Zhang, Yong; Fu, Wen-Bo (Frontiers in Medicine, 2024)
Prevotella is often considered a Bacteroides complex associated with a healthy plant-based diet that acts as a “probiotic” throughout the body’s entire digestive tract from the mouth to the anus. Previous studies have not reported that this “probiotic” colonizing the human body could cause severe pneumonia. This case report describes a 56-year-old healthy female worker with gum pain followed by fever. Despite prompt medical attention given by the use of empirical antibiotics and tooth and oral cleaning, the disease rapidly progressed to retropharyngeal abscess and severe pneumonia. Although the surgeon performed pharynx and cervical incisions and drainage, the patient’s symptoms were not significantly relieved. After repeated blood culture and sputum culture, no positive findings were found. Fortunately, Prevotella oris was found in the peripheral blood of the patient by metagenomic next-generation sequencing (mNGS). The disease was controlled quickly by changing the targeted antibiotics according to the guidelines for the detection of pathogenic bacteria. Three months after discharge, the patient’s symptoms did not resolve, and reexamination with computerized tomography (CT) showed that the neck and chest were normal. This case is unique in that it shows that normally colonized Prevotella oris could also cause fatal pneumonia as an opportunistic pathogen. Our goal is to highlight that serious infections that rapidly develop from common symptoms in an era of widespread antibiotic use not only increase patient misunderstanding but also lead to over detection and testing of such symptoms by clinicians. Expanding the pathogenic characteristics of special pathogens through the literature and using accurate mNGS may be the technical tool for resolving this contradiction.